Exploring the influence of ChatGPT to UTAR broadcasting students - Yong, Pei En (2024)
This study aims to explore the influence of ChatGPT to the UTAR broadcasting students. This study utilizes qualitative method to obtain findings and data through semi-structured interviews. Semi-structured interviews are used to collect narrative data like their experience, thoughts, and feelings in a non-numeric way. There are a total of five interviewees who are UTAR broadcasting students had been chosen through purposive sampling participated in this research interview. The findings of this study fulfil the objectives: (1) To discuss the benefits of UTAR broadcasting students in using ChatGPT; and (2) To understand the challenges and concern of UTAR broadcasting students in using ChatGPT. The benefits of using ChatGPT according to the interviews include: (1) Convenience; (2) Time-saving; (3) Brainstorming; (4) Language efficiency; (5) Doing research; and (6) Gain knowledge and skills. Furthermore, the concerns and challenges of using ChatGPT: (1) General and limited; (2) Accuracy of answer; (3) Risk of plagiarism; and (4) Excessive reliance in using ChatGPT. This study consists of limitations as in the sample size is small, which may not represent all UTAR broadcasting students. Moreover, it is recommended for a longer time duration for deeper analysis. Lastly, future studies are also recommended to investigate a wider range of broadcasting students.